Could myocardial function be predictive of successful extubation in newborns and infants?. Issue 6 (23rd February 2021) - Massolo, Anna C.; Clemente, Maria; Patel, Neil; Cantone, Giulia V.; Toscano, Alessandra; Ficial, Benjamim; Landolfo, Francesca; Calzolari, Flaminia; Capolupo, Irma; Biban, Paolo; Dotta, Andrea
Abstract: Objective: To investigate the relationship between cardiac function and extubation readiness in infants using speckle tracking echocardiography. Working hypothesis: Cardiac function combined with established clinical parameters may better identify readiness for extubation. Study Design: Pilot prospective observational study. Patient selection: Mechanically ventilated infants were included. Methodology: Cardiac function was assessed by echocardiography immediately before extubation. Systolic and diastolic function in the left (LV) and right ventricles (RV) were assessed by measurement of longitudinal strain (LS), and circumferential strain (CS) in the LV only. Pulmonary artery pressures were assessed using the velocity of tricuspid regurgitation jet (TR), septal position, and end‐systolic eccentricity index (EI ES). Cases who extubated successfully (Group 1) were compared to cases who required reintubation (Group 2). Results: Twenty‐five cases were included. LV CS and RV LS were significantly lower in those who required reintubation (Group 2) compared to those who were successfully extubated (Group 1) (LV CS, −21 (12)% vs. −33 (3)%, p = .001; RV LS −19 (2.7)% vs. −20 (2.5)%, p = .04). TR was absent in all cases. The septal shape was normal in 18 cases (72%), displaced to the left in 7 (28%) cases. No significant differences were found in LV EI ES between groups.